The Concept of Social (In)Justice and Its Portrayals in Todd Phillips’s Joker - Çöteli, Sami (Communication Today, 2020)
The main objective of the present study is to reflect on the problem of social justice and the ways it is portrayed in Joker (2019, directed by Todd Phillips). A discourse analysis is used in order to identify the particular elements of social injustice and social unrest within the movie in question. Social injustices which were deeply felt within the atmosphere of the movie and the social explosion which followed social injustices instigated asocial movement. Contrary to the general belief, the social movement was identified with tyranny. By designating the social movements as illegal, the movie established a type of identification which would attribute legitimacy to homicides. Being just and having equal opportunities in the distribution of societal resources come to the forefront. This ‘web’ of relations signifies the position of the individual and society vis-à-vis the state, and assures that the individual enters into the public sphere. Along with the disparity and the lack of resources in terms of equal opportunities, an individual’s attitude follows a positive or negative path in the public sphere. In the movie Joker, a world in which the concept of social justice had fallen apart was pictured. By establishing identification with Joker’s psychological disorders, the social movement which was experienced hereby was presented as a tyranny to the moviegoers. In this study, together with the analysis of the movie, the concepts of “social justice” and “social movement” will be discussed.